FAUNA AND ECOLOGY OF HELMINTHS IN CATTLE (BOS TAURUS DOM.) OF CENTRAL UZBEKISTAN - M. E. Gaipova; F. D. Akramova; K. A. Saparov; D. A. Azimov; U. A. Shakarbaev (Российский паразитологический журнал, 2016)
Objective of research: The purpose of research is to study the fauna and ecology of helminths in cattle from Central Uzbekistan.Material and methods. The cattle was investigated by the method of complete and incomplete helminthological autopsies. Cestodes, trematodes and nematodes were examined using the common methods. Larvae of trematodes and nematodes from dominant parasite species found in intermediate hosts (molluscs, insects, ants and dipterous) are also described in this paper.Results and discussion: 32 helminth species were identified in cattle from the central region of Uzbekistan: 5 species belong to the class Cestoda, 6 species — to the class Trematoda and 21 species — to the class Nematoda. Based on the nature of helminth localization in the host body, three groups of parasite communities were detected.